THE USE OF INTERACTIVE TEACHING METHODS IN MEDICAL EDUCATION IN HIGHER EDUCATION INSTITUTIONS - Qurbonova Munisa; Maksudova Malika; Nadirova Yulduz (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Modern medical education faces the challenge of preparing highly competent, critical-thinking, and patient-centered healthcare professionals. Traditional lecture-based teaching methods are increasingly considered insufficient for developing clinical reasoning, communication skills, and lifelong learning habits required in contemporary medical practice. This article explores the role of interactive teaching methods in higher education for medical students. Based on scientific literature and international educational standards, the paper analyzes the effectiveness of interactive methods such as problem-based learning, case-based learning, simulation-based education, team-based learning, and digital interactive tools. The findings demonstrate that interactive methodologies significantly improve students’ academic performance, clinical competence, motivation, and professional skills. The article concludes that integrating interactive teaching methods into medical curricula is essential for improving the quality of medical education.